2015
DOI: 10.1073/pnas.1514138112
|View full text |Cite|
|
Sign up to set email alerts
|

Tissue mechanics govern the rapidly adapting and symmetrical response to touch

Abstract: Interactions with the physical world are deeply rooted in our sense of touch and depend on ensembles of somatosensory neurons that invade and innervate the skin. Somatosensory neurons convert the mechanical energy delivered in each touch into excitatory membrane currents carried by mechanoelectrical transduction (MeT) channels. Pacinian corpuscles in mammals and touch receptor neurons (TRNs) in Caenorhabditis elegans nematodes are embedded in distinctive specialized accessory structures, have low thresholds fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
150
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(167 citation statements)
references
References 60 publications
(120 reference statements)
15
150
2
Order By: Relevance
“…Amiloride-sensitive Na Ï© currents were rapidly elicited in touch receptor neurons at the onset and removal of a mechanical force (23). This fast adapting transient current is sensitive to body indentation as well as the velocity and frequency of stimulus but not the amount of the applied force (40). We found that LSS elicited a robust activation of MEC-4/MEC-10 channels (2-3-fold increases in whole cell Na Ï© currents) expressed in Xenopus oocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Amiloride-sensitive Na Ï© currents were rapidly elicited in touch receptor neurons at the onset and removal of a mechanical force (23). This fast adapting transient current is sensitive to body indentation as well as the velocity and frequency of stimulus but not the amount of the applied force (40). We found that LSS elicited a robust activation of MEC-4/MEC-10 channels (2-3-fold increases in whole cell Na Ï© currents) expressed in Xenopus oocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Through these improvements, which included a switch to the Intracellularly, gradients in vinculin tension have been reported in cells adhered to micropost arrays, 276 although tension asymmetries were mainly attributed to the presence of the discontinuous substrates 277 (Sarangi et al, 2017). We show that these asymmetric molecular loads, high at the distal tips and low at (Saez et al, 2005) and that strain determines the activation of touch-sensitive channels in in 288 vivo models (Eastwood et al, 2015). However, while vinculin appears to be under extension-control in…”
mentioning
confidence: 81%
“…Given that the anterior and posterior TRNs detect forces in the nano-Newton to micro-Newton range 35,36 , we delivered force pulses with values between 50 nN and 10,000 nN. We measured forceresponse curves at three anterior body positions (25%, 35%, and 45% of the distance from the head), and two posterior positions (55% and 75% of the distance from the head).…”
Section: Tactile Sensitivity Varies Within and Between Receptive Fieldsmentioning
confidence: 99%